Analisis Fungsi dan Makna Nyanyian Rohani Batak Toba dalam Dua Konteks Ibadah Kristen di Medan - Simamora, Samaria; Naiborhu, Torang; Fadlin, Fadlin (Mahesa Research Center, 2025)
This research aims to describe and analyze the function of Batak Toba sacred songs in the Charismatic worship of GBI Mawar Saron, Simalingkar B, and in the worship of HKBP Pardomuan, Simalingkar B, Medan. It also seeks to identify and compare the meanings contained in Batak Toba sacred songs within Charismatic and HKBP traditional worship, as well as to examine how the functions and meanings of these songs transform when used in different worship contexts. The researcher employs a qualitative-descriptive approach using observation, interviews, and documentation conducted directly at the selected research sites. The theoretical framework applied in this study includes Alan P. Merriam’s theory of the functions of music and Jean-Jacques Nattiez’s musical meaning analysis. The findings indicate that there are significant changes in musical style, song presentation, and worship structure, revealing differences in the liturgical and expressive functions between the two churches. Nevertheless, Batak Toba sacred songs continue to serve as a medium of spiritual unity and cultural identity among the congregations. Through this study, the researcher hopes to contribute to the field of ethnomusicology and enhance cross-traditional understanding within the practice of Christianity in Indonesia.